From Bias to Better Decisions: Behavioral Insights for Financial Literacy Curriculum Development in Higher Education - Yuliawati, Tia; Nurhayati, Netti Siska; Abdul Aziz, Nor Farradila; Nugraha; Sari, Maya; Purnamasari, Imas; Harisandi, Prasetyo (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the effect of behavioral bias on investment decisions of undergraduate students in Indonesia in the context of higher education with risk perception as a mediating variable and financial literacy as a moderating variable as a basis for strengthening the behavioral-based financial literacy curriculum in universities, as well as preparing students to become rational investors. Method: The study used a quantitative approach by distributing questionnaires to 385 undergraduate students in Indonesia who are active individual investors and registered with the Kustodian Sentral Efek Indonesia (KSEI). The structural model analysis was conducted using SmartPLS 4, while the moderated mediation test was performed using PROCESS Model 59 in SPSS. Results: The study's results indicate that behavioral bias has a significant adverse effect on risk perception, which in turn hurts the investment decisions of students in Indonesia. Financial literacy is proven to act as an important moderating variable. It can weaken the adverse effect of behavioral bias on risk perception and change the impact of risk perception on investment decisions to be positive at high levels of financial literacy. In addition, risk perception mediates the relationship between behavioral bias and investment decisions, especially at moderate levels of financial literacy. Novelty: The findings underscore the importance of integrating behavioral aspects in developing financial literacy curricula in higher education to equip students with the cognitive and affective competencies needed for rational investment decision-making. This study contributes to the behavioral finance literature and offers practical and theoretical contributions for educators and policymakers in designing contextual and behavioral-based financial literacy education for students.